Peningkatan Kemampuan Berpikir Kritis dan Hasil Belajar Melalui Model Pembelajaran Stad dengan Peta Konsep Materi Pencemaran Air di SMP N 3 Slawi - Indri Puspita Sari; Antonius Tri Widodo; Muriani Nur Hayati (Universitas Pancasakti Tegal, 2020)
This study aims to improve cognitive learning outcomes, critical thinking skills, and determine students' responses to the STAD type cooperative model with the concept map media. The study uses a Pre Test Post Test Comparation Group Quation Experiment Design. The sampling technique using Cluster Random Sampling, obtained 2 sample classes namely control class 32 experimental class 32. Data collection techniques using questionnaires, documentation, and tests. The research instrument was tested for validity and reliability. The data analysis technique uses Independent Sample T Test. The results showed a significant difference from the critical thinking skills and learning outcomes, namely the average value of the Post Test critical thinking ability of the experimental class 74.94 higher than the average value of the Post Test control class 65.78 and the average value of the Post Test learning outcomes cognitive experimental class 82.97 higher than the average value of the control class Post Test 66.75. There is an increase in the average N-Gain critical thinking of the experimental class 0.47 the moderate category is greater than the control class 0.2 the low category, while the cognitive learning outcomes of the experimental class 0.65 the medium category is greater than the control class 0.29 the low category. The results of students 'responses differed significantly between the experimental class and the control class, where the STAD learning model with concept maps can improve cognitive learning outcomes and students' critical thinking abilities.